The Impact of Covid 19 Pandemic on Consumer Behavior Delivery Services in Malaysia and Indonesia - Phing Shuin Liew; Wei Ning Liew; Cia Shim Lim; Jenq Yang Lin; Salwa Inka Qonitah (Asia Pacific Journal of Management and Education (APJME), 2022)
The Covid 19 pandemic causes people to reduce physical interactions as everyone is encouraged to keep a safe distance to reduce the spreading of the virus. During this pandemic, as cities are locked down, e-commerce has become a trend, and therefore, a delivery company like Delivery Services is needed in order to deliver items purchased by customers to their homes. The objective of the study is to find out the impact of the Covid 19 pandemic on consumer behavior towards the intention to use Delivery services. The data were collected from a survey questionnaire about the consumer behavior in Malaysia and Indonesia towards courier company of Delivery Services. This study was gathered data from 100 consumers through Google Form. The findings of this research reveal that consumer intention to use the courier services increased during the Covid 19 pandemic.